An Assessment of the Literature and Recent Developments on the Shallow Wake in an Open Channel Flow - Arindam Singha; Ramaswami Balachandar (Advances in Civil Engineering)
Although shallow flows are very abundant both in nature and in flows of technological importance, their effective characterization started only recently. This type of flow, being vertically confined, exhibits some unique features, which are absent in conventional unconfined flows. A brief review of the related research articles indicates that the exploration of the shallow wake had occurred in three distinct chronological phases. Initially, almost all investigations were aimed at exploring the differences between shallow flows and unconfined flows. Given the differences, the second phase of investigations was mostly concerned with identifying the sources of these differences found already. The third and most recent group of investigations attempted to correlate the flow topology with the extent of the confinement and focused on more applied areas like control of wake instability and consequent effects on drag reduction, and the effect of the coherent structures on species transport. The present paper is intended to present retrospect of the seminal investigations regarding shallow flows, and summarizes the key results from widely ranging studies. Another motivation of the present paper is to provide a basis for future research of shallow wake.